Preliminary investigation of the determinants of FDI distribution in Italy - Pazienza, Pasquale; Vecchione, Vincenzo (Journal of Business Economics and Management, 2009)
The debate on the structural competitiveness of national and local productive systems has lately paid relevant attention to the territorial distribution of Foreign Direct Investment (FDI), since it can be perceived as an indicator of economic openness and integration in the world market. With regard to this, it can be observed that Italy has a strong potential for attracting investment, but the inward flow of FDI is very small with respect to what happens in other countries. This study analyses the factors determining this kind of mismatch with the aim of identifying appropriate policy suggestions to improve the strategies to attract foreign investors to Italy and, particularly, to its southern regions. First Publish Online: 14 Oct 2010